Kandungan Lipid Total Nannochloropsis oculata Pada Kultur dengan Berbagai Fotoperiod (Total Lipid Content of Culture of Nannochloropsis oculata at Different Photoperiod) - Widianingsih Widianingsih; Retno Hartati; Endrawati Hadi; Valentina R Iriani (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2012)
Fotoperiod memainkan peranan penting dalam proses fotosintesis pada mikroalga Nannochloropsis oculata. Fotoperiod akan mempengaruhi kadar total lipid pada berbagai jenis mikroalga. Penelitian ini bertujuan untuk determinasi kandungan lipid total mikroalga Nannochloropsis oculata yang dikultur pada berbagai kondisi fotoperiod Rancangan acak lengkap dengan tiga ulangan diterapkan pada penelitian ini. Perlakuan pada penelitian ini adalah fotoperiod 4 jam terang-20 jam gelap, 8 jam terang-16 jam gelap, 12 jam terang-12 jam gelap, dan 24 jam terang. N. oculata dikultur pada erlenmeyer 250 mL dengan sistem aerasi kontinyu dan pencahayaan 3000 lux, salinitas 33 ppt dan medium Conway. Hasil penelitian menunjukkan bahwa kandungan lipid total pada N. oculata tertinggi ditemukan pada perlakuan fotoperiod 12 jam terang-12 jam gelap) (31,8±3,03%-dw) dan kemudian diikuti pada fotoperiod 8jam terang - 16 jam gelap (25,2±2,19%-dw) dan fotoperiod 24 jam terang (23,2 %-dw). Pada perlakuan fotoperiod 8 jam terang-16 jam gelap dan fotoperiod 12 jam terang-12 jam gelap pada media pemeliharaan N.oculata menunjukkan hasil kadar lipid total yang lebih besar pada fase stasioner dibandingkan dengan eksponensial.Kata kunci: Nannochloropsis oculata, total lipid, fotoperiodPhotoperiod has important role on the photosynthesis process of microalgae Nannochloropsis oculata. Photoperiod also influences on total lipid content of various microalgae. This research has purpose to examine the effect of nutrient phosphate and nitrate composition to the total lipid content of N. oculata belong to class Eustigmatophyceae. There were four treatments of photoperiod as follows; (a) photoperiod A (4:20 hour light:dark);(b) photoperiod B (8:16 hour light:dark); photoperiod C (12:12 hour light:dark); (and (d) photoperiod D (24 hour light). There were three replicates for each treatment. The volume of culture medium was 250 mL for each treatment with continuously aeration and illumination (3000 lux). According to the research, the highest total lipid content of N. oculata had been found on the treatment of photoperiod 12:12 hour light:dark 31,8 ± 3,03 %-dw, and then followed by photoperiod 8:16 hour light dark as amount 25,2 ± 2,19 %-dw and 24 hour light (23,2 ± 1,99%-dw), and then followed by photoperiod 24 hour light. Differences of photoperiod 8:16 hour light:dark and photoperiod 12:12 hour light:dark on culture medium of N. oculata showed result that there were differences of total lipid content on the stationary and exponential phase. The highest percentage of total lipid was fund in cell of N. oculata grown under treatment of photoperiod 12:12 hour light:dark. The treatment of photoperiod 8:16 hour light:dark and 12:12 hour light:dark in the N. oculata culture showed result that the total lipid content on stationary phase was greater than exponential phase.Key words: Nannochloropsis oculata, total lipid, photoperiod